FACTORS AFFECTING PROFITABILITY OF SHARIA COMMERCIAL BANKS IN INDONESIA - Astuty, Widia; Pasaribu, Mhd Husein (Proceeding International Seminar of Islamic Studies, 2024)
This study aims to empirically prove the factors that affect profitability in Islamic Banks in Indonesia seen from the Islamicity Performance Index as measured by Profit Sharing Ratio, Zakat Performance Ratio, and Islamic Income Ratio. This study uses an associative approach while the data collection technique uses documentation from the Otoritas Jasa Keuangan (OJK) through http://www.ojk.go.id. The population of this study is 12 Sharia Commercial Banks in Indonesia registered with the Otoritas Jasa Keuangan (OJK) from 2021 to 2022. The data analysis technique uses multiple linear regression analysis. The results of this study show that the Profit-Sharing Ratio variable affects profitability, while Zakat Performance Ratio, and Islamic Income Ratio do not affect profitability.